2010
DOI: 10.2478/v10131-010-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Individualities of Cardiorespiratory Responsiveness to Shifts in Respiratory Homeostasis and Physical Exercise in Homogeneous Groups of High Performance Athletes

Abstract: It is known that high sports performances are based upon optimization of adaptation process. In order to achieve the above, one should provide aidual vivid features of athlete's abilities, peculiarities of his/her physiological reactivity. The aim was to study individualities of sensitivity to shifts in respiratory homeostasis and responsiveness to high intensity physical exercises in homogeneous groups of high performance endurance athletes. Individual peculiarities of the cardiorespiratory system (CRS) physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(31 reference statements)
0
5
0
2
Order By: Relevance
“…Alongside with it we should not deny role of power, kinetic and other anaerobic energy supply components in the process of training work, considering importance of aerobic metabolism for optimization of sportsmen's functional state. It is especially important in period of fulfillment of great training loads, including with training of special endurance with anaerobic work [9]. The trend to connection of speed of HBR progressing indicators is connected with high tension of organism's functions and only indirectly determines responsive potentials of rowers (aerobic metabolism or response of lung ventilation).…”
Section: Results Of the Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside with it we should not deny role of power, kinetic and other anaerobic energy supply components in the process of training work, considering importance of aerobic metabolism for optimization of sportsmen's functional state. It is especially important in period of fulfillment of great training loads, including with training of special endurance with anaerobic work [9]. The trend to connection of speed of HBR progressing indicators is connected with high tension of organism's functions and only indirectly determines responsive potentials of rowers (aerobic metabolism or response of lung ventilation).…”
Section: Results Of the Researchmentioning
confidence: 99%
“…Alongside with it, it was shown that identical programs of trainings caused different energy supply responses and, as a result, differences in effectiveness of training process [9]. There appeared an idea that in process of training, oriented on development of rowers' functional potentials, specific features of organism acquire special importance, features, which influence on realization of accumulated potential [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Значно зросла конкуренція і, як наслідок, напруженість змагальної боротьби. Тому в системі підготовки боксерів все більше уваги приділяється не тільки вдосконалення їх спеціальних умінь і навичок, а й тих сторін підготовленості кваліфікованих спортсменів, які дозволяють підтримувати високий рівень працездатності в умовах підвищеного напруження функціонального забезпечення змагальної діяльності [1] і, в тому числі, в умовах прогресуючого стомлення [1,9,12,14].…”
Section: вступunclassified
“…Фахівці, що займаються вивченням жіночого спорту, вказують на необхідність враховувати специфічні вимоги до функціонального забезпечення спеціальної витривалості жінок-боксерів [5,16,21]. При цьому високий ступінь специфічності прояву функціональних можливостей спортсменок характеризується зміною реактивних властивостей організму, які можуть бути охарактеризовані за реакцією кардіореспіраторної системи на наростання ацидемічних зрушень в організмі в умовах фізичних навантажень різного характеру енергозабезпечення [8,10,12,13,14].…”
Section: вступunclassified